How do customers perceive the brand image of Nagad, and why customers are considering the Nagad app to purchase insurance policy premiums as their preferred payment method - Mahbuba, Tasneem (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.